Information and Communications Technology (ICT) and agricultural extension in developing countries - Spielman, David J.; Lecoutere, Els; Makhija, Simrin; Van Campenhout, Bjorn (International Food Policy Research Institute, 2021)
Our study focuses on a narrow class of ICT products and services: technologies related to mobile phones, services, and networks; portable devices; web-based portals, tools, and applications; and the data and information shared through these products and services via technologies as varied as interactive voice response (IVR) systems and satellite imagery. We do not consider more traditional ICTs such as radio and television programming. In addition, we focus on a core function of extension services—the promotion of productivity-enhancing agricultural technologies and practices—from which we examine the impacts of ICT-enabled extension on equity outcomes, such as changes in women’s empowerment and decision-making within households; on behavioral outcomes, such as aspiration, risk, and ambiguity preferences; and on learning outcomes, such as awareness, knowledge, and learning externalities.